Front Cover: Improving Antibody‐Tubulysin Conjugates through Linker Chemistry and Site‐Specific Conjugation (ChemMedChem 7/2021). (8th April 2021) - Hamilton, Joseph Z.; Pires, Thomas A.; Mitchell, Jamie A.; Cochran, Julia H.; Emmerton, Kim K.; Zaval, Margo; Stone, Ivan J.; Anderson, Martha E.; Jin, Steven; Waight, Andrew B.; Lyon, Robert P.; Senter, Peter D.; et al.
Abstract : The Front Cover shows the antimitotic tubulysin M bound to bovine brain tubulin. Highlighted in yellow is the labile C11 acetate, the loss of which leads to greatly reduced biochemical activity. The corresponding article interrogates the effect of drug‐linker chemistry and conjugation site on the stability of this acetate and the in vivo activity of antibody–drug conjugates (ADCs) delivering tubulysin M. The results led the team from a protease cleavable 4‐load ADC (top) to an optimized β‐glucuronidase cleavable 2‐load ADC (bottom). More information can be found in the Communication by Joseph Z. Hamilton et al .